New Automated Storage and Retrieval System (ASRS) using wireless communications - Rashid, Muhammad Mahbubur; Kasemi, Banna; Rahman, Mahmudur (Institute of Electrical and Electronics Engineers ( IEEE ), 2011)
This study proposes a new design of an Automated Storage and Retrieval System (ASRS) using wireless communication. The highlight of this project is to aid and improve existing warehouse management system (WMS) that occupies manpower, on-paper data recording and non-intelligent machines during the operation. The essence of this project is to implement wireless technology in controlling ASRS system. Microcontroller and other electronics modules give designer the capability to control movement and rotation of the motor while PIC16F877A programming aid the ASRS movement based on its condition and position of each of the parts that move. The communication between PIC controller and computer is made by a wireless technology. The motion of the system is based on three DC motors, one for each direction of motion X, Y and Z, controlled through PIC microcontroller. The experiment with the prototype shows the success in placing the object to the right destination as requested by the user within shorter time which reveals the success of this study. This automated system is highly demanded in large factories such as automotive factories and mass production companies to aid inventory management system in the warehouse and huge storage area due to the time consumption and dramatic cost reduction factors.